Seguimiento del Plan de Gestión Integral de Residuos Sólidos (PGIRS) de la empresa Triturados Paz de Río (2023)
This project is carried out from the follow-up of the Integral Solid Waste Management Plan (PGIRS) of Triturados Paz de Río S.A. S; through information presented in reports of environmental documents and accompaniment of activities focused on the subject to process them in checklists in order to determine the nature of the same if it is a PGIRS according to Resolution 754 of 2014 or PGIRESPEL based on Decree 4741 of 2005, on the other hand, through a verification matrix of compliances the Program of Integral Management of Hazardous Waste is identified, Finally, the Waste Management Plan has the structure of a PGIRESPEL but is implemented as a PGIRS (i.e. the two types of plans are linked). Additionally, with respect to the waste management programs, it is concluded that in terms of quality, place, time and social group indicators, the results are satisfactory to date; however, the same is not true for the quantity indicators because the minimization of hazardous and solid waste generation does not decrease, but rather increases due to the arrival of waste from other sites and an increase in personnel.